USING TERLIPRESSIN AIMED TO REDUCE BLOOD LOSS IN CESAREAN SECTION - Yu. S. Аleksandrovich; A. V. Rostovtsev; E. S. Kononova; O. V. Ryazanova; T. I. Аkimenko (Вестник анестезиологии и реаниматологии, 2019)
The objective of the study: to assess the impact of the agonist of vasopressin receptor V-1 (terlipressin) in the operative delivery of obstetric patients with a high risk of hemorrhage during cesarean section.Subjects and methods. 60 women were examined, all of them had planned cesarean section; the median age made 32.7 years and gestation time made 38 weeks. Group 1 (n =30) included patients who underwent surgery without terlipressin; Group 2 (n =30) included women who had 0.4 mg of terlipressin intra-operatively introduced endometrially (into the place of the uterus incision) immediately after omphalotomy. The volume of the blood loss was measured intra-operativelly. The arterial tension and hemodynamic rates were assessed during the surgery and in 24 hours after it in the morning.Results. It was found out that there was a statistically significant difference in the volume of intra-operative blood loss and need for blood transfusion. Using terlipressin resulted in the reduction of blood loss by 37–50% which was due to its pharmacological effects, i.e. vasoconstrictive and antihemorrhagic ones.Conclusions. Using terlipressin within comprehensive intensive care during cesarean section in the patient facing the high risk of hemorrhage allows reducing the intra-operative blood loss to a significant extent and reducing transfusion of donor blood components.